Thursday

August 28, 2014

August 28, 2014

Posted by **Ann** on Thursday, April 3, 2014 at 11:53pm.

please explain how to solve this

- Calculus -
**Steve**, Friday, April 4, 2014 at 12:09amSince f(2) = -21,

f^-1(-21) = 2

f'(x) = -6x^2-3

(f^-1)'(-21) = 1/f'(f^-1(-21)) = 1/f'(2) = -1/27

**Related Questions**

calculus (gr 12) - Evaluate each of the following. Show all your calculations. a...

calculus (gr 12) - Evaluate each of the following. Show all your calculations. a...

Grade 12 Calculus - Evaluate each of the following. Show all your calculations...

biology - Given the part of the molecule shown below, can the underlined atom ...

Maths-Calculus - If f(2)=1 and f(2+h)=(h+1)3, compute f′(2). If f(−...

Product of Roots of Sums of Products of Difference - What is the product of all ...

math - Consider the following 6 relations on the set of real numbers: A) y=2x&#...

linear algebra - solve using gauss jordan 10y − 4z + w = 1 x + 4y − ...

math - The number 27+200−−−√−−−−...

Math - PreCalc (12th Grade) - If Sn = 1 + 6 + 11 + 16 + 21 + 26...... where an...